Weaknesses of the territorial administrative model at the level of the department and municipality that favor inefficiency in the public administration (2017)
In the search for the common wellness above individual interests, it must necessarily be referred to the most important treasure that possesses a nation’s resources; these are sacred because they originate from the contributions of all citizens, who in various ways contribute to the performance, progress, and economic development of a nation. But, what happens when these resources are used irresponsibly and it is evidenced in inefficient management, what leads to waste and abuse by those who have under their responsibility the duty to manage them; It is then when it is required to give a voice of warning that causes to analyze the short comings of our territorial organizational model, the permissibility towards inefficient management of these resources, and anything which helps the non-achieving of the desired outcomes for the citizens.